2003
DOI: 10.1089/109264203321235494
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Paracecal Hernia Repair

Abstract: The diagnosis and treatment of internal abdominal hernia usually require laparotomy. We report a case of preoperative diagnosis and laparoscopic repair of paracecal hernia. A 90-year-old woman was referred with features of a well-established small bowel obstruction (SBO). Computed tomography and a small bowel contrast examination showed a paracecal hernia. With the patient under general anesthesia, laparoscopic surgery was carried out with the use of pneumoperitoneum, and an easy reduction of the incarcerated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 5 publications
0
19
0
3
Order By: Relevance
“…On reviewing these three case reports [3,8,9] all were performed after several days of conservative treatment which had not responded, in comparison to our patient who was operated on within 24 hours. All the cases showed viable bowel upon reduction of the hernia and no resections were required.…”
Section: Discussionmentioning
confidence: 78%
“…On reviewing these three case reports [3,8,9] all were performed after several days of conservative treatment which had not responded, in comparison to our patient who was operated on within 24 hours. All the cases showed viable bowel upon reduction of the hernia and no resections were required.…”
Section: Discussionmentioning
confidence: 78%
“…Of these, only two cases were reportedly diagnosed by the laparoscopic procedure. 2,3 Only one of these two cases was successfully treated by laparoscopic surgery and achieved a good postoperative course. 2 The other case was converted to open surgery in order to avoid injury to the small intestine.…”
Section: Discussionmentioning
confidence: 99%
“…2 The other case was converted to open surgery in order to avoid injury to the small intestine. 3 Laparoscopic surgery is therefore considered suitable for early diagnosis and minimally invasive treatment of paracecal hernias. Some studies have reported enlarging the opening pouch as well as closing the orifi ce in order to avoid recurrence of the hernia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though all of the studies are of low LE, the potential role of laparoscopy in the diagnosis seems to be demonstrated in them and would, at times, prevent unnecessary laparotomies [298][299][300][301][302][303][304][305][306][307][308][309][310][311][312][313][314][315][316][317].…”
Section: Incarcerated/strangulated Herniasmentioning
confidence: 99%